Transformasi Cerita Serat Menak dalam Pertunjukan Wayang Golek Menak - Tatik Harpawati (Gelar : Jurnal Seni Budaya, 2009)
The change of form from written literature to performing arts produces a new genre, for the reason, transformation of all intrinsic as well extrinsic aspects are complex and varied the changes in performing arts which come from serat menak show that serat menak has had transformation. Concerning that serat menak is adaptation form Hikayat Amir, it is not impossible that artists of wayang golek menak may base their works directly form the original work. The aims of this discussion include (1) describing story (lakon) wayang golek menak; (2) describing transformation forms of serat menak in lakon wayang golek menak covering character, setting, story, and theme; (3) mapping the development of serat menak in lakon wayang golek menak. The aims will be fulfilled by using reception and intertextual approaches approaches. Based on both approaches, it can be found out that serat menak becomes the source of some stories (lakon) in wayang golek menak. Transformation of story can be seen in the hiprogramming stories in serat menak. Story pattern in wayang golek menak manak have double characters. Transformation of setting can be found in the addition and different names of places where the story happens. Transformation of character appears in the change of name and the additional new names for not basic characters. The difference and addition of name, place and character occur because of the different pronounciation, miss information, as well as the dalang creativities in recept serat menak. The reason is that the performance of wayang golek menak is inherited orally so that the development of serat menak in lakon wayang golek menak is very extensive and complex. Dalang can freely create lakon in accordance to his view and his family as well as social cultural background.Keyword : Transformation, Serat Menak, Wayang Golek Menak